2021
DOI: 10.3390/math10010044
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Interval Type-2 Fuzzy MCDM Framework for the Resilient Supplier Selection Problem

Abstract: Selecting the most resilient supplier is a crucial problem for organizations and managers in the supply chain. However, due to the inherited high degree of uncertainty in real-life projects, developing a decision-making framework in a crisp or fuzzy environment may not present accurate or reliable results for the managers. For this reason, it is better to evaluate the potential suppliers in an Interval Type-2 Fuzzy (IT2F) environment for better dealing with this ambiguity. This study developed an improved comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Therefore, to prioritize the suppliers, they identified criteria and used ISM and DEMATEL methods in the fuzzy environment to check the most effective criteria. Hoseini et al, (2021b) defined resilient supplier selection as a challenging problem for the supply chain management. They defined sub-criteria for the main criterion of resilience and used BWM and TOPSIS methods to prioritize suppliers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to prioritize the suppliers, they identified criteria and used ISM and DEMATEL methods in the fuzzy environment to check the most effective criteria. Hoseini et al, (2021b) defined resilient supplier selection as a challenging problem for the supply chain management. They defined sub-criteria for the main criterion of resilience and used BWM and TOPSIS methods to prioritize suppliers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, considering resilience when choosing a supplier increases the ability to control the supply chain when disruptions occur. Also, the resilient supply chain can protect various industries from disruptions and facilitate the return to the original state (Hoseini et al, 2021b). The concept of resilience should be developed in the supply chain to overcome potential disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…They validated their proposed model in a therapy equipment supply chain of a company and suggested some managerial insights for the managers in the recent pandemic. Hoseini et al ( 2022 ) proposed a framework for resilient supplier selection problem while considering uncertainty through interval type-2 fuzzy (IT2F) environment. They also used best–worst method and compared the results with analytical hierarchy process (AHP) and simple additive weighting (SAW) approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In supplier selection problems, Celik et al ( 2019 ) found the most suitable supplier IT2F-BWM and TODIM. Hoseini et al ( 2021 ) used BWM in combination with TOPSIS. IT2F-BWM has been widely used in solving risk assessment problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Verbal expressions evaluating risk factors were modeled with the help of type-2 fuzzy numbers. The priorities of failures were determined with IT2FBWM Hoseini et al ( 2021 ) Supplier selection TOPSIS For the evaluation of potential suppliers in Iranian construction industry, criterion weights were determined with IT2FBWM and supplier evaluation with type-2 fuzzy TOPSIS Norouzia and Hajiagha ( 2021 ) Numerical example NA The method is proposed by combining BWM hesitant and interval type-2 fuzzy sets. A numerical example is given to demonstrate the effectiveness of the proposed method Celik and Gul ( 2021 ) Risk assessment MARCOS Risk weights are weighted with IT2FBWM and hazards are prioritized with MARCOS Chen et al ( 2022 ) Hospital selection Data envelopment analysis (DEA) This study was carried out in the TrIT2F environment, which will combine BWM and DEA, and select the reasonable sites of makeshift hospitals …”
Section: Literature Reviewmentioning
confidence: 99%